Late-onset rash in patients with group A beta-hemolytic streptococcal pharyngitis treated with amoxicillin - Masahiko Kimura (MDPI AG, 2015)
We observed late-onset rashes in patients with group A beta-hemolytic streptococcal (GAS) pharyngitis. Of 1028 patients with GAS pharyngitis, which was principally treated with amoxicillin, we evaluated those who developed a late-onset rash and excluded those with scarlet fever alone. Twenty-one patients developed a rash (2.0%, 95% confidence interval, 1.3- 3.1%), 7 to 20 days (median, 8 days) after GAS pharyngitis onset. The rashes were characterized by maculopapules, which increased in size with coalescence and some developing into plaques, with a symmetrical distribution with a propensity for the extremities, including the palms and soles. The clinical courses of the patients were good, and the rashes subsided within 14 days. A non-immediate reaction to β-lactams, which usually manifests as a maculopapular rash, is a possible cause in our patients, however, repeated courses of amoxicillin in 3 patients did not induce the rash. The underlying mechanism of the late-onset rash after GAS pharyngitis with amoxicillin treatment remains unclear.